2011
DOI: 10.3747/co.v18i4.737
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy for Advanced Gastric Cancer: A Clinical Practice Guideline

Abstract: • Within a combination chemotherapy regimen, oral capecitabine is preferred over intravenous 5-fluorouracil (5fu)-that is, epirubicin-cisplatincapecitabine is preferred over the prior standard regimen, epirubicin-cisplatin-5fu (ecf).• Epirubicin-oxaliplatin-capecitabine (eox) is a reasonable alternative to ecf. The choice between ecf and eox should be based on patient preference.• Trastuzumab in combination with cisplatin and a fluoropyrimidine (5fu or oral capecitabine) is recommended for advanced gastric can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…The latest publication data from the World Health Organization (WHO) and International Arctic Research Center (IARC) indicate that the incidence of gastric cancer is 952,000 worldwide and 405,000 in China, accounting for 42.6% of the global incidence 3. In China, most of the patients are diagnosed in advanced stages of gastric carcinoma, ~10% patients are at the early stage of gastric cancer, and the 5-year survival rate is 10%–30% 4. Gastric resection with D2 lymph node dissection is the mainstay of treatment in advanced gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The latest publication data from the World Health Organization (WHO) and International Arctic Research Center (IARC) indicate that the incidence of gastric cancer is 952,000 worldwide and 405,000 in China, accounting for 42.6% of the global incidence 3. In China, most of the patients are diagnosed in advanced stages of gastric carcinoma, ~10% patients are at the early stage of gastric cancer, and the 5-year survival rate is 10%–30% 4. Gastric resection with D2 lymph node dissection is the mainstay of treatment in advanced gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Oxaliplatin however, has been investigated as an alternative to cisplatin in some tumour types. For example, oxaliplatin-based regimens have been recommended as an alternative to cisplatin-based therapy for the treatment of advanced gastric cancer 58 . Studies have also reported comparable outcomes to cisplatin-based therapy with reduced toxicity for advanced non-small-cell lung cancer 59 .…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…MacKenzie [32] and the Gastrointestinal Cancer Disease Site Group (2011)sought to determine the optimal chemotherapy for gastric cancer in its advanced stages. The study came up with various recommendations, which included the following.…”
Section: Adjuvant Chemoradiotherapymentioning
confidence: 99%